Protecionismo e medidas sanitárias e fitossanitárias nas exportações avícolas brasileiras - Goebel, Márcio Alberto (2022)
The constant increase in international trade in the last decades has triggered the debate around food health and the activation of Non-Tariff Measures (NTM) mechanisms raised by the members of the World Trade Organization (WTO) in 1995. One component of this mechanism is the agreement on Sanitary and Phytosanitary Measures (SPS), which aims to regulate trade relations between countries based on rules that support food safety. Several researches and studies have tried to explain the WTO mechanisms, the existence of protectionism in its use, and also to measure the impacts that such measures have on the alteration of exports and prices in the commercialization of food. Not very dissimilar, this thesis intended, based on a Systematic Bibliographical Review (SBR) and the use of secondary data, within a descriptive perspective, to verify the existence of SPS measures specifically for the Brazilian poultry sector from the 4-digit Harmonized System (HS) (0207) and if in any analysis any atypical behavior could be verified in relation to the exports of this product. The results showed an increasing number of SPS notifications in the WTO since its creation in 1995, which happens in parallel with the growth of world exports, except in historical moments of global economic crisis, as happened in the decades 2000 and 2010, considering effects in close years. Brazil also stands out as one of the largest users of the WTO notification system, but also suffers from a high number of questionings, most frequently from the European Union. By analyzing the questioning that Brazil suffers in relation to poultry exports, it was found that there was a drop in the collection of the amounts exported of this animal protein, even though the volumes exported continued to grow moderately. The research also provided the understanding that the sector is competitive and gives the understanding that the problems related to the barriers imposed by exporting countries are solved within firms.